British Crime Survey, 1992 ([Verlag nicht ermittelbar], 1996)
The fourth in a series of surveys instituted by the Home Office in 1982, this survey examines levels of victimization in Great Britain and offers attitudinal data on issues relating to crime. The 1992 survey was intended to replicate the 1982, 1984, and 1988 surveys (ICPSR 8672, 8685, and 9850) in methodology and content as much as possible. In 1992, a "core" sample of 10,059 adults along with booster samples of 1,650 ethnic minority adults and 1,350 young people aged 12-15 resident in the same households as adult respondents were interviewed. The 1988 survey had also included an ethnic minority booster sample employing the same sampling method. Respondents were asked a series of screening questions to establish whether they had been the victims of crime during the reference period, and another series of detailed questions about the incidents they reported. Basic descriptive background information, such as sex, age, employment, education, and number of children, was also collected on the respondents and their households. Other information was elicited on fear of crime, contact with the police, lifestyle, and self-reported offending. Part 1, Demographic File, consists of data captured on the Demographic Questionnaire. Parts 2 and 3 represent data collected via Follow-Up Questionnaire A and Follow-Up Questionnaire B, respectively. Each respondent completed one of the two Follow-Up Questionnaires, with all respondents in the ethnic minority booster sample completing Follow-Up Questionnaire A. Part 4, Main File, consists of data from the Main Questionnaire. Each respondent completed a Main Questionnaire that included some attitudinal questions and a large number of screening questions to identify crime victims. Data in Part 5, Victim File, were collected from the Victim Form. Only respondents reporting incidents of victimization on the Main Questionnaire have Victim Forms, with up to four Victim Forms per respondent. The unit of analysis for this collection is the individual.